Using secondary prevention strategies in patients after PCI: a narrative review - Xi, Guangdi; Yang, Fuguo; Xu, Jianan; Liu, Jingzhe; Chen, Dexin (Frontiers in Public Health, 2025)
ObjectiveThe objective of this review is to integrate the content and effectiveness of secondary prevention interventions in post-PCI patients so that provide direction for the selection of more effective secondary prevention measures in the future.MethodA narrative review was performed, which included a literature search without language and study design restrictions in PubMed, Embase, and MEDLINE from January 1, 2000, to May 15, 2023. Search terms included free-text words for the key concepts of “Percutaneous Coronary Intervention” “PCI” and “secondary prevention”.ResultsThis study consolidated the measures of secondary prevention included in the studies and found that patient education strategies had the highest rate of use (78%), followed by exercise (56%), with smoking cessation, diet, blood pressure control, and medication also being used in the remainder. We critically analyzed these secondary prevention strategies and found that only 56% of these secondary preventions were effective in their use, with the remaining 44% having non-significant differences between the intervention and control groups. 44% of the studies incorporated mHealth, and mHealth had a facilitating effect on the intervention. We found that patients had better results on subjective measures after surgery (p < 0.05), while none of the objective measures were significant.ConclusionThis study found that the use of secondary prevention in post-PCI patients is not limited to medication; five non-pharmacologic measures, namely patient education, exercise, dietary modification, blood pressure control, and smoking cessation, have also been actively used. Some studies have combined mHealth technology with secondary prevention measures with good results, in which the interactivity of mHealth should be focus on. However, changes in objective prognostic measures after the application of secondary prevention measures in post-PCI patients were not significant, indicating that the efficacy of the measures was not significant, which is an issue that deserves to be emphasized in subsequent studies. Meanwhile, educational, economic, and social support challenges in the older adult population may hinder the effective implementation of secondary prevention, future studies in the older adult population should prioritize addressing these issues to optimize the prognosis of older adult patients.